Passiflora Incarnata L. Herba in the Treatment of Anxiety Symptoms and Insomnia in Children and Adolescents with Feeding and Eating Disorders - Angela La Tempa; Giulia Ferraiuolo; Beatrice Pranzetti; Jacopo Pruccoli; Antonia Parmeggiani (Adolescents)
Background: Feeding and Eating Disorders (FEDs) are severe mental health conditions often emerging during childhood or adolescence, with rising prevalence. They are frequently associated with psychiatric and organic comorbidities, including anxiety symptoms and insomnia. Phytotherapy, particularly Passiflora incarnata L. Herba, has been suggested as a potential treatment option for anxiety and insomnia in youth. Methods: this is an observational and retrospective study that includes patients assessed in a third-level Italian Regional Centre for Feeding and Eating Disorders in Children and Adolescents between 1 January 2020 and 31 December 2023. Eligible patients had a confirmed diagnosis of a FED, along with either an anxiety or a sleep disorder. During follow-up, the clinical efficacy of Passiflora incarnata L. Herba was assessed using the Clinical Global Impression–Improvement scale (CGI-I). Comparative analyses were conducted by stratifying the sample based on the target symptoms (sleep disorders/insomnia and anxiety), FED subtype, and whether polytherapy was used. Results: this study includes 94 patients, with most diagnosed with anorexia nervosa (71.3%). Passiflora incarnata L. Herba was administered at a dosage of 200 mg (1–2 tablets for day). It was often combined with selective serotonin reuptake inhibitors (SSRIs) (56.5%), atypical antipsychotics (27.7%), or benzodiazepines (7.4%). Treatment was initiated for anxiety symptoms (75.5%) or insomnia (28.7%). No side effects were reported. Among patients with specific outcome data, 53.3% reported improvements in anxiety symptoms, and 45.4% reported improvements in insomnia. Conclusions: this is the first study to evaluate the use of Passiflora incarnata L. Herba for anxiety and insomnia in children and adolescents with FEDs. Our findings suggest that Passiflora incarnata L. Herba may serve as a well-tolerated adjunctive treatment, showing symptomatic improvement in up to 53% of the patients with data on treatment outcomes. Notably, 53.3% and 45.4% of participants, with specific outcome data, reported reduced anxiety and insomnia symptoms, respectively. Given its excellent safety profile and preliminary efficacy, Passiflora incarnata L. Herba may represent a promising alternative for patients with mild symptoms or for caregivers hesitant about conventional pharmacotherapy.